(untitled) (Research, Society and Development, 2021)
The objective of this study was to develop flours with almond (FAM) and mango peel (MF), cultivate Tommy Atkins, characterize its physical-chemical and microbiological properties, determine antioxidant activity and develop brownie using the flours. Also, identify the volatile compounds present in flours, brownies and cocoa. A traditional chocolate brownie was prepared and with the replacement of 70% of the wheat flour by the mixture of the flours obtained. The MF and MF presented themselves as sources of nutrients, with emphasis on the high content of dietary fibers (average of 37%), and safe from the microbiological point of view. In addition, MF and MF are rich in phenolic compounds (4,495 and 3,340 mg AGE/100 g) and have high antioxidant activity. The brownie prepared with the flour mixture presented a nutritional profile with higher value of fibers, lipids and calories than the traditional one. Considering all samples analyzed, 32 volatile compounds were identified. In the flours were found compounds of the classes of terpenes, aldehydes and ester. In the brownies, in addition to the classes mentioned, alcohols, pyrazins and fatty acids were identified in the traditional. In cocoa, hydrocarbons, pyrazins, terpenes, aldehydes, alcohols and esters were found. Thus, it can be affirmed that the use of mango co-products is safe from a microbiological point of view, contributes to the nutritional and functional enrichment of preparations, as well as to the reduction of discarded residues in the environment.